Answer: x=+25
Step-by-step explanation:
(5x+4)=(8x-71)
first move all terms to the left:
(5x+4)-((8x-71))=0
second get rid of parentheses
5x-((8x-71))+4=0
Third calculate terms in parentheses: -((8x-71)), so:
(8x-71)
Fourth get rid of parentheses
8x-71
5th to the equation:
-(8x-71)
6th get rid of parentheses
5x-8x+71+4=0
7th add all the numbers together, and all the variables
-3x+75=0
8th move all terms containing x to the left, all other terms to the right
-3x=-75
x=-75/-3
x=+25x=+25x=+25x=+25x=+25x=+25x=+25